2020
DOI: 10.1007/s11427-020-1859-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response and therapy in COVID-19 patients: what can be learned for vaccine development?

Abstract: The newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected millions of people and caused tremendous morbidity and mortality worldwide. Effective treatment for coronavirus disease 2019 (COVID-19) due to SARS-CoV-2 infection is lacking, and different therapeutic strategies are under testing. Host humoral and cellular immunity to SARS-CoV-2 infection is a critical determinant for patients’ outcomes. SARS-CoV-2 infection results in seroconversion and production of anti-SARS-CoV-2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 194 publications
(324 reference statements)
1
31
0
1
Order By: Relevance
“…The results of this study, which analyze the temporal dynamics of anti-SARS-CoV-2 antibodies in CCP donors during their repeat donations, are in line with those reported in the literature [4]. For instance, in a previous study on 494 consecutive CCP donors we have demonstrated that COVID-19 severity was associated with greater antibody responses [7].…”
Section: Dynamics Of Anti-sars-cov-2 Antibodies In Repeat Convalescent Plasma Donorssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study, which analyze the temporal dynamics of anti-SARS-CoV-2 antibodies in CCP donors during their repeat donations, are in line with those reported in the literature [4]. For instance, in a previous study on 494 consecutive CCP donors we have demonstrated that COVID-19 severity was associated with greater antibody responses [7].…”
Section: Dynamics Of Anti-sars-cov-2 Antibodies In Repeat Convalescent Plasma Donorssupporting
confidence: 89%
“…Although short-term seroprevalence studies have consistently demonstrated a seroconversion of IgG, IgA and IgM antibodies against viral spike and nucleocapsid proteins within 1-3 weeks after symptom onset and a rapid decline of IgM and IgA titers [3], less information is available about the long-term course of neutralizing anti-SARS-CoV-2 IgG antibodies [4]. This topic has not only speculative value but can also have important practical implications for vaccine development and administration schedule, in order to provide an adequate and long-lasting immune response against SARS-CoV-2 in vaccinated people [4]. In addition, understanding the dynamics of anti-SARS-CoV-2 antibodies is critical to collect the most appropriate plasma units from individuals recovered from COVID-19 (COVID-19 convalescent plasma, CCP).…”
Section: Dynamics Of Anti-sars-cov-2 Antibodies In Repeat Convalescent Plasma Donorsmentioning
confidence: 99%
“…Clinical characterization protocols are now being collected on patients worldwide to better define the illness, in terms of its natural history, mode of transmission, clinical profiles, management, and specific risk factors, to prevent or overcome the damaging effects of the disease 9 , 17 . What is known so far is that a significant proportion of individuals infected by COVID-19 remain asymptomatic and are thus an unbeknownst potential source of infection 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“… 2020 ; Zhang et al . 2020 ). In our study, we used two viral concentrations and tried to simulate the viral titers present in patient respiratory samples.…”
mentioning
confidence: 99%